Nutritional and physiological responses of the dicotyledonous halophyte Sarcocornia fruticosa to salinity - Garcia-Caparros, Pedro (2019)
Sarcocornia fruticosa (L.) A.J. Scott is a dicotyledonous halophyte that grows in areas with an arid climate such as the marshes of southern Spain. The species has potential uses for saline agriculture and biofuel production, but the effects of salt stress on its nutrition and physiology remain unclear. Plants of S. fruticosa were grown in pots with a mixture of sphagnum peat-moss and Perlite. In order to evaluate the effects of different levels of salinity, five treatments using different NaCl concentrations (10 (control), 60, 100, 200 and 300 mM NaCl) were applied over a period of 60 days. At the end of the experiment, the dry weight, the biomass allocation and the tissue water content were measured for each salinity treatment. The net uptake of various nutrients and their translocation rates were calculated for each salt treatment. Salt loss, shedding of plant parts and succulence in shoots were evaluated together with the K+/Na+ ratio, K-Na selectivity, concentrations of osmolytes and their estimated contributions to the osmotic potential. Our results showed that S. fruticosa can maintain its major physiological processes at 60 mM NaCl without significant dry weight reduction. Higher salinity resulted in negative values for net uptake and translocation rates from roots to shoots of N and P. As might be predicted from other dicotyledonous halophytes, S. fruticosa plants increased Cl- and Na+ uptake using both as osmotica instead of organic osmolytes. However, to survive salinity, this species has also evolved others mechanisms such as shedding old shoots, increased succulence in shoots at higher salt concentrations and the ability to maintain a lower K+/Na+ ratio and higher K-Na selectivity in all organs.